2019
DOI: 10.18502/kls.v4i13.5311
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Hip and Knee Strengthening on Reducing Pain Intensity among Elderly with Osteoarthritis

Abstract: Background:The population of elderly people increases from year to year along with increasing life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
1
0
0
1
Order By: Relevance
“…A significant statistical difference in pain level was identified before and after knee exercise with p=0.004. This is following the results of research by Marlina (2015) and Marlina, et al, (2019) which confirmed that knee exercises were effective to reduce knee pain among patients with knee osteoarthritis. Regular knee exercise promotes blood circulation and metabolism in the patella region.…”
Section: Discussionsupporting
confidence: 84%
“…A significant statistical difference in pain level was identified before and after knee exercise with p=0.004. This is following the results of research by Marlina (2015) and Marlina, et al, (2019) which confirmed that knee exercises were effective to reduce knee pain among patients with knee osteoarthritis. Regular knee exercise promotes blood circulation and metabolism in the patella region.…”
Section: Discussionsupporting
confidence: 84%
“…The Crossfit Journal Article (2016) mengemukakan bahwa untuk meningkatkan fleksibilitas otot dan sendi, stretching sangat efektif dilakukan karena dapat memberikan efek penurunan nyeri persendian. Latihan aktivitas fisik (stretching) dapat meningkatkan aliran darah dan memperkuat tulang (Rahmiati, 2017), Sejalan dengan penelitian dengan judul The Effectiveness of Hip and Knee Strengthening on Reducing Pain Intensity among Elderly with Osteoarthritis dengan hasil bahwa pemberian intervensi Strengthening efektif dapat mengurangi intensitas nyeri (Marlina & Sr Lucilla, 2019).…”
Section: Pendahuluanunclassified